Measurement of green industrial performance: an enhanced GIP index. (26th May 2020) - Alba, Jaime Moll De; Todorov, Valentin
The green industrial performance (GIP) index provides a tool to analyse and compare the performance of economies in terms of green manufacturing. The demands for and expectations for sustainable development seem not matched with the existence of an analytical framework to measure how green the industrial sector of a given economy is. In this article, we introduce significant methodological improvements to the GIP index. In previous research, we developed and tested a set of indicators covering the various facets of the green industrial performance of economies. We also introduced a composite index to rank economies according to their green industrial performance. In this article, we address some limitations of the index. To improve the non-satisfactory data coverage, we investigate alternative imputation methods. We also refine our list of 'green' products; and test new outlier detection methods.